Determination of Probiotic Potential and Anticancer Activity of Lactobacillus Isolated from Cheese and Yogurt - Muthanna Hamid Hassan (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, microorganism was isolated from cheese and yogurt, cultured on specific culture media, thenrecognized molecularly through 16S rDNA f quality sequencing. The supernatant of Lactobacillus strainscontained probiotic activity such as anticancer effects against cancer cell lines such as HeLa, RD and normalcell line (REF )cells and antibacterial. The cytotoxicity effects were assessed by MTT stain and apoptosis inmitochondria. The supernatant showed had anticancer activity against the tested cell lines (P< 0.05) with nosignificant cytotoxic effects against normal cell line .